Learning from peers' stock prices and corporate investment - Foucault, Thierry; Fresard, Laurent (Journal of Financial Economics, 2014)
Peers' valuation matters for firms' investment: a one standard deviation increase in peers' valuation is associated with a 5.9% increase in corporate investment. This association is stronger when a firm's stock price informativeness is lower or when its managers appear less informed. Also, the sensitivity of a firm's investment to its stock price is lower when its peers' stock price informativeness is higher or when demands for its products and its peers' products are more correlated. Furthermore, the sensitivity of firms' investment to their peers' valuation drops significantly after going public. These findings are uniquely predicted by a model in which managers learn information from their peers' valuation.